2017
DOI: 10.1128/aac.00732-17
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic Emergence in the United States of Escherichia coli Sequence Type 131- H 30 (ST131- H 30), 2000 to 2009

Abstract: The H30 subclone of Escherichia coli sequence type 131 (ST131-H30) has become the leading antimicrobial resistance E. coli lineage in the United States and often exhibits resistance to one or both of the two key antimicrobial classes for treating Gram-negative infections, extended-spectrum cephalosporins (ESCs) and fluoroquinolones (FQs). However, the timing of and reasons for its recent emergence are inadequately defined. Accordingly, from E. coli clinical isolates collected systematically across the United S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…Fifth, our novel ST1193-H64 PCR-based assay was simple and accurate and so should facilitate the molecular epidemiological studies needed to further assess the prevalence, ecology, and clinical significance of ST1193-H64. Regarding clonal emergence, several recent reports have documented ST1193-H64 as an emerging contributor to the FQ-R E. coli population (7)(8)(9)(10)(11)(12)(13), usually second only to ST131-H30, which in contrast emerged globally beginning nearly 2 decades ago (6,24,(36)(37)(38)(39)(40). Our findings suggest a staggered timing for the emergence of ST1193-H64 at different centers, with historical isolates from Australia dating to 2008; a low prevalence in 2011 in Olmsted County, MN, and at VAMCs nationally in the United States; and a later appearance at MVAMC (2013), followed by a rapid rise and then a plateau and even a possible decline (fecal colonization).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifth, our novel ST1193-H64 PCR-based assay was simple and accurate and so should facilitate the molecular epidemiological studies needed to further assess the prevalence, ecology, and clinical significance of ST1193-H64. Regarding clonal emergence, several recent reports have documented ST1193-H64 as an emerging contributor to the FQ-R E. coli population (7)(8)(9)(10)(11)(12)(13), usually second only to ST131-H30, which in contrast emerged globally beginning nearly 2 decades ago (6,24,(36)(37)(38)(39)(40). Our findings suggest a staggered timing for the emergence of ST1193-H64 at different centers, with historical isolates from Australia dating to 2008; a low prevalence in 2011 in Olmsted County, MN, and at VAMCs nationally in the United States; and a later appearance at MVAMC (2013), followed by a rapid rise and then a plateau and even a possible decline (fecal colonization).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular typing. Established multiplex PCR-based assays were used to identify E. coli phylogroups (22), nine clonal subsets (including STc14) within group B2 (23), ST131 and its H30R subclone (5), 50 E. coli virulence genes (24), and the O75 and O18 antigen-encoding rfb regions (25). Clonal typing was done for all FQ-R isolates (clinical and fecal), all FQ-S isolates from the University of Minnesota and Olmsted County, a random 25% subsample of non-ST131 group B2 FQ-S MVAMC clinical isolates through April 2017 and all such isolates thereafter, and selected FQ-S MVAMC fecal surveillance isolates.…”
Section: Methodsmentioning
confidence: 99%
“…Increasing rates of cephalosporin resistance have been reported among these pathogens and a main reason is because of the dissemination of ESBLs, particularly CTX-M-15 and CTX-M-14, depending on the geographic region (5,12). Another important contributor to the rising rates of antimicrobial resistance is the dissemination of E. coli ST131, particularly the H30Rx subset, which often displays resistance to broad-spectrum cephalosporins and fluoroquinolones (7,8). A previous study reported an occurrence of 45% of ST131 among E. coli isolates in 2009 in the United States (7).…”
Section: In Vitro Activity Of Tebipenem Antimicrobial Agents and Chemmentioning
confidence: 99%
“…The spread of a specific E. coli clone that is defined by phylogenetic group B2, serotype O25:H4, and multilocus sequence typing (MLST) 131 has also been identified as an important contributor to the epidemic of antimicrobial resistance in hospital and community settings, especially for first-line agents, such as fluoroquinolones and broad-spectrum cephalosporins (7)(8)(9). This epidemiologic shift has great implications for the empirical management of community-associated UTIs; therefore, oral agents to treat outpatients at high risk for infections caused by ESBL-producing pathogens or inpatients who could benefit from step-down therapy would become valuable assets in the antimicrobial armamentarium.…”
mentioning
confidence: 99%
“…[2][3][4][5] Molecular epidemiologic studies have shown that a subclone of ST131, termed H30, has driven the global dissemination of ST131. [6][7][8][9] The clonal structure of ST131-H30 is tightly linked to antimicrobial resistance; the vast majority of H30 isolates are fluoroquinolone resistant due to mutations in the gyrA and parC chromosomal genes (isolates known as H30-R or clade C), while nested subclones are additionally associated with the production of CTX-M-type extended-spectrum beta-lactamases (ESBLs) that confer resistance to extended-spectrum cephalosporins ( Figure S1). [7,8,[10][11][12] Although E. coli ST131-H30 (hereafter, H30) has been recognized as a clone of significant public health importance, [5,13] there is a lack of data about its epidemiology in children.…”
Section: Introductionmentioning
confidence: 99%